Experimental study on the phase formation of MgxB2 (x=0.8, 1.0, 1.2) - Mohd Aris, Mohd Faisal; Shaari, Abdul Halim; Chen, Soo Kien; Abd Shukor, Roslan; Awang Kechik, Mohd Mustafa; Ahmed, Malik Idries Adam; Lim, Kean Pah; Mansor, Mohd Kamarulzaman; Ravandi, Saeedeh Sadat Hosseini; Baqiah, Hussein Abdullah Hussein; Ng, S. W. (Ibnu Sina Institute for Fundamental Science Studies, 2009)
Phase formation of Magnesium diboride Mgx B2(x=0.8, 1.0, 1.2) by in situ reaction of Magnesium (Mg) and Boron (B) at different annealing temperature by varying the nominal Mg composition was compared. The X-ray difffraction pattern indicates that Magnesium Oxide (MgO) is the major secondary phase. Some unreacted Mg was found for nominally stoichiometric and Mg excess samples annealed at or below 750°C. However, no unreacted Mg was detected by XRD for Mg deficient samples. Scanning Electron microscopy images show the porous nature of synthesised samples.